The truth according to ember ebook - Nava, Danica (2024)
A Chickasaw woman who can’t catch a break serves up a little white lie that snowballs into much more in this USA Today bestselling rom-com by critically acclaimed author Danica Nava. Ember Lee Cardinal has not always been a liar—well, not for anything that counted at least. But her job search is not going well and when her resumé is rejected for the thirty-seventh time, she takes matters into her own hands. She gets “creative” listing her qualifications and answers the ethnicity question on applications with a lie—a half-lie, technically. No one wanted Native American Ember, but white Ember has just landed her dream accounting job on Park Avenue (Oklahoma City, that is). Accountant Ember thrives in corporate life—and her love life seems to be looking up as well: Danuwoa Colson, the IT guy and fellow Native who caught her eye on her first day, seems to actually be interested in her too. Despite her unease over the no-dating policy at work, they start to see each other secretly, which somehow makes it even hotter? But when they're caught in a compromising position on a work trip, a scheming colleague blackmails Ember, threatening to expose their relationship. As the manipulation continues to grow, so do Ember’s lies. She must make the hard decision to either stay silent or finally tell the truth, which could cost her everything.